The point-slope formula is
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
where m is the slope of a line passing through the point (x₁, y₁).
Also, the slope m of a line passing through points (x₁, y₁) and (x₂, y₂) is
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/78uaqhwt0aws3qfwxigaftpihnmb1gzxtp.png)
In this problem, the line passes through points (4, -3) and (-2, 5). Thus, we have:
x₁ = 4
y₁ = -3
x₂ = -2
y₂ = 5
Then, the slope is
![m=(5-(-3))/(-2-4)=(5+3)/(-6)=(8)/(-6)=-(4)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/fcaskveg7b88s9uaq7ksemo6e5kttaxlx5.png)
And the equation in point-slope form is
![y-(-3)=-(4)/(3)(x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/epckuiqw3dtbw9d3rnel9nay6jpb9ex8iy.png)
Now, we need to rewrite this equation in slope-intercept form. The slope-intercept equation of a line with slope m and y-intercept b is
![y=mx+b](https://img.qammunity.org/2023/formulas/mathematics/high-school/smsb8cbft03lwblmi49nf2l6jby2ofxzws.png)
Thus, we need to isolate y on the left side of the equation to obtain the slope-intercept form, as follows:
![\begin{gathered} y+3=-(4)/(3)x-(4)/(3)(-4)\text{ using the distributive property of multiplication over addition} \\ \\ y+3=-(4)/(3)x+(16)/(3) \\ \\ y+3-3=-(4)/(3)x+(16)/(3)-3 \\ \\ y=-(4)/(3)x+(16)/(3)-(9)/(3) \\ \\ y=-(4)/(3)x+(7)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a7j8n5dwj1lcdhhrc5g7oh224rvmppxsxq.png)
Therefore, the slope-intercept form of that linear equation is
![y=-(4)/(3)x+(7)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/gsnwmu08s8yxmt0lycd5ityofswe4mah9y.png)